Evaluasi Pembelajaran BTHQ Kibar di Masa Pandemi Covid-19 di SMP Mugadeta Muhammadiyah 3 Depok - Finna Baity Janah; Muqowim Muqowim; Hasbiyallah Hasbiyallah (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
The covid-19 pandemic made the learning process, especially BTHQ learning done remotely. This can make the ability of learners affected. In this case, tentors or educators in this BTHQ activity play an important role in improving and developing cognitive value skills in learners under any circumstances. Therefore, every educator must have a high level of desire so that the implementation of BTHQ in the Covid-19 pandemic can run properly and can improve cognitive abilities in learners. This study aims to identify the extent of the role of educators in evaluating BTHQ Kibar in learners during the covid-19 pandemic and to find out what factors affect the cognitive ability of learners in BTHQ kibar activities during the covid-19 pandemic so that the BTHQ learning process (Read Quran Memorization) can continue. In research using a qualitative descriptive approach, i.e. the data collected in the form of words, images, and not numbers. The results showed that BTHQ activities provide knowledge, understanding, how to read well using the letter makharijul, provide advice or motivation for children to follow BTHQ in a timely manner, provide punishment that educates learners, and conduct evaluations after BTHQ activities.